The Performance of Socially Responsible Investments: A Meta-Analysis - Lars Hornuf; Gül Yüksel (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this article, we use a meta-analysis to examine the performance of socially responsible investing (SRI). After a thorough literature search, we review 153 empirical studies containing 1,047 observations of SRI performance. We find that, on average, SRI neither outperforms nor underperforms the market portfolio. However, in line with modern portfolio theory, we find that global SRI portfolios outperform regional sub-portfolios. Moreover, high-quality publications, publications in finance journals, and authors who publish more frequently on SRI are all less likely to report SRI outperformance. In particular, we find that including more factors in a capital market model reduces the likelihood that a study will find SRI outperformance. These findings have important implications for the policy evaluation of environmental, social, and governance goals in general, the asset management literature in particular, and the perspective of different scientific disciplines.
Keywords: G11; G12; M14; 330; environmental social governance; ESG; socially responsible investment; SRI; meta-analysis